Comprehensive and molecular phytopathology (Elsevier, 2007)
This book offers a collection of information on successive steps of molecular dialogue between plants and pathogens. It additionally presents data that reflects intrinsic logic of plant-parasite interactions. New findings discussed include: host and non-host resistance, specific and nonspecific elicitors, elicitors and suppressors, and plant and animal immunity. This book enables the reader to understand how to promote or prevent disease development, and allows them to systematize their own ideas of plant-pathogen interactions.